A Systematic Review of Amino Acid-Based Adsorbents for CO2 Capture - Nur Syahirah Mohamed Hatta; Mohamed Kheireddine Aroua; Farihahusnah Hussin; Lai Ti Gew (Energies, 2022)
The rise of carbon dioxide (CO2) levels in the atmosphere emphasises the need for improving the current carbon capture and storage (CCS) technology. A conventional absorption method that utilises amine-based solvent is known to cause corrosion to process equipment. The solvent is easily degraded and has high energy requirement for regeneration. Amino acids are suitable candidates to replace traditional alkanolamines attributed to their identical amino functional group. In addition, amino acid salt is a green material due to its extremely low toxicity, low volatility, less corrosive, and high efficiency to capture CO2. Previous studies have shown promising results in CO2 capture using amino acids salts solutions and amino acid ionic liquids. Currently, amino acid solvents are also utilised to enhance the adsorption capacity of solid sorbents. This systematic review is the first to summarise the currently available amino acid-based adsorbents for CO2 capture using PRISMA method. Physical and chemical properties of the adsorbents that contribute to effective CO2 capture are thoroughly discussed. A total of four categories of amino acid-based adsorbents are evaluated for their CO2 adsorption capacities. The regeneration studies are briefly discussed and several limitations associated with amino acid-based adsorbents for CO2 capture are presented before the conclusion.